Hearing Performance and Soft-Tissue Outcomes of Minimally Invasive Ponto Surgery and Local Anesthesia in Children with Unilateral Craniofacial Malformation - Leone, Andrea Caruso; Castilho, Arthur Menino; Danieli, Fabiana; Calil, Daniela Bortoloti; Almeida, Katia de (International Archives of Otorhinolaryngology, 2025)
Introduction Minimally invasive Ponto surgery (MIPS) enables the installation of percutaneous bone-anchored hearing implants (BAHIs) with a drill guide through a hole punch incision. Despite being well established for adults, there is a lack of studies in the literature regarding its use in pediatric patients.Objective The aim of the present study was to investigate the hearing performance and soft-tissue outcomes of the use of MIPS under local anesthesia in children with unilateral craniofacial malformation (UCM).Methods The study used a retrospective cohort design. Nine subjects with UCM, aged between 6.5 and 17.1 (median = 12) years, who underwent the MIPS procedure under local anesthesia were included. Surgical procedure, intra, and postoperative complications were investigated. Speech recognition thresholds in quiet (SRTQ) and in noise (SRTN), daily use, satisfaction, and perceptual listening effort of the subjects were assessed after 4 months of postoperative follow-up.Results It was possible to perform MIPS under local anesthesia in 8 of 9 subjects, with no intraoperative complications. One subject (11.11%) showed adverse skin reactions during a mean follow-up period of 11.4 months with MIPS. Speech recognition thresholds in quiet, SRTN, and subjective listening effort scores significantly decreased with the use of BAHI. The subjects were overall satisfied with the device and using it 8.2 hours/day, on average.Conclusion Under local anesthesia, MIPS showed to be a viable option for BAHI installation in children with UCM. The hearing performance of the subjects improved, and they were globally satisfied with the device. Soft-tissue complications were minimal, and our results are comparable to those reported in the literature for adults.
Keywords: bone conduction; minimally invasive; bone drilling; craniofacial abnormalities; bone-anchored prosthesis; children